Adoption of Improved Management Practices of Sugarcane in Bara and Nawalparasi Districts - Bhattarai, Anuma; Sigdel, Udit Prakash; Dhital, Pankaj Raj; Shrestha, Ram Krishna; Timilsina, Srijana (Journal of Agriculture and Environment, 2023)
Agricultural technologies have an important role to improve productivity as well as the quality of the crops.However, the adoption of improved technology has remained poor for sugarcane in Nepal. A research was conducted in Bara and Nawalparasi (Bardhaghat Susta west (BSw)) district of Nepal with a sample for 120 sugarcane growing farmers in the year 2019 to assess adoption of improved management practices of sugarcane. Descriptive statistics and inferential statistics were used to of improved management practices among farmers. Respondents were grouped into two categories, high adopter and medium adopter based on adoption index of each farmer. The average Adoption Index (AI) value obtained was 0.685. Around fortywere high adopters. The use of credit, ownership of agri-machine, and participation. All variables had a positive relationship with the level of adoption of improved practices. The study revealed that farmers using credit, ownership of power-driven agri-machine, participation in crop related training increased the probability of farmer being high adopter. Agricultural machinery services, easy and cheap credit facilities and, easy access to extension services can help to increase in adoption of improved practices by sugarcane farmer.